Anti-MOG Positive Bilateral Optic Neuritis and Brainstem Encephalitis Secondary to COVID-19 Infection: A Case Report - Zisis Tsouris; Antonios Provatas; Christos Bakirtzis; Athina-Maria Aloizou; Vasileios Siokas; Vana Tsimourtou; Nikolaos Grigoriadis; Georgios M. Hadjigeorgiou; Efthimios Dardiotis (MDPI AG, 2022)
(1) Introduction: There have been numerous reports on the neuroinvasive competence of SARS-CoV-2. Here, we present a case with anti-MOG positive bilateral optic neuritis and brainstem encephalitis secondary to COVID-19 infection. Additionally, we present a review of the current literature regarding the manifestation of anti-MOG positive optic neuritis as well as anti-MOG positive encephalitis after COVID-19 infection. (2) Case Report: A 59-year-old female patient, with a recent history of COVID-19 infection, presented a progressive reduction of visual acuity and bilateral retrobulbar pain for the last 20 days. An ophthalmological examination revealed a decreased visual acuity (counting fingers) and a bilateral papilledema. An MRI scan of the brain revealed a mild thickening of the bilateral optic nerves and high-intensity lesions in the medial and right lateral pons. A high titer of IgG and IgM antibodies against SARS-CoV-2 in serum and antibodies against myelin oligodendrocyte glycoprotein (anti-MOG) in serum and CSF were revealed. The diagnosis of anti-MOG brainstem encephalitis and optic neuritis was set. (3) Conclusions: The history of COVID-19 infection should raise awareness about these autoimmune and infection-triggered diseases, such as anti-MOG antibody disease.